Physiological features of the antioxidant system of the Equus caballus organism of different genotypes - Petrus K. Amulungu; Aleksandr V. Tkachev; Olga L. Tkacheva (RUDN Journal of Agronomy and Animal Industries)
In modern physiology, the features of the functional state of the body are increasingly being studied not in terms of breeds, age, and animal husbandry technologies, but in terms of DNA markers. Therefore, in this aspect, it is interesting to compare the functional state of the antioxidant system of the Equus caballus organism depending on the breed and DNA markers. The purpose of this study was to conduct a comparative analysis of the functional state of the antioxidant system of Equus caballus horses of different breeds and with different genotypes according to the GRM8 gene. The study of the physiological characteristics of the antioxidant system of the body of Equus caballus of Russian breeding was carried out from 2005 to 2023. The study involved 70 breeding stallions belonging to 9 breeds. The best superoxide dismutase activity was detected in the blood of stallions with the CC/AA genotype according to SNPrs395286150/394524550: 11.4 and 2.3% more ( p 0.05) than in carriers of the CT/AG and TT/GG genotypes, respectively. Catalase (CAT) activity was at a comparable level but with significant differences. We observed the highest CAT activity in the blood of stallions with the CC/AA genotype according to SNPrs395286150/394524550, which is 1.8% more in carriers of the CT/AG genotype and 7.9% ( p 0.05) more in carriers of the TT/GG genotype. Against this background, the activity of glutathione peroxidase (GPx) was the highest in the blood of stallions carrying the CT/AG genotype according to SNPrs395286150/394524550, which is 9.8% more ( p 0.05) in stallions of the CC/AA genotype and 14.8% more ( p 0.01) in stallions of the TT/GG genotype. The amount of malondialdehyde (MDA) was highest in carriers of the GG genotype according to SNPrs1147388106, which is 13.4% more ( p 0.01) in carriers of the GA genotype and 2.6% more in carriers of the AA genotype according to SNPrs1147388106. The study of the functional state of the antioxidant system of the horse body, depending on the breed, also shows the presence of significant differences between breeds of different uses.